Keeping up with the Joneses, reference dependence, and equilibrium indeterminacy - Livio Stracca; Ali al-Nowaihi (European Central Bank (ECB), 2005)
This model extends the keeping up with the Joneses (KUJ) model to incorporate the notion that positional concerns in consumption are best modelled with a reference dependence specification of preferences, as postulated by Tversky and Kahneman (1991) in the context of riskless choice. In line with this specification, which has received substantial empirical support in the literature, we assume that the marginal returns on the own consumption are increasing below the aggregate per capita levels of consumption (which is the reference point in our model). The main conclusion of the paper is that in our KUJ model aggregate consumption may be subject to sunspot fluctuations and the equilibrium level of consumption is not uniquely pinned down. The paper also discusses the role that fiscal policy can play in order to undo the effect of consumption externalities on both the determinacy and the desirability of the equilibrium.
Keywords: D11; H21; 330; Consumption externalities; equilibrium indeterminacy; keeping up with the Joneses; optimal taxation; reference dependence; Nachfrageinterdependenz; Gleichgewichtstheorie; Theorie